Topoisomerase 2B Decrease Results in Diastolic Dysfunction via p53 and Akt: A Novel Pathway - Moudgil, Rohit; Samra, Gursharan; Ko, Kyung Ae; Vu, Hang Thi; Thomas, Tamlyn N.; Luo, Weijia; Chang, Jiang; Reddy, Anilkumar K.; Fujiwara, Keigi; Abe, Jun-ichi (Frontiers in Cardiovascular Medicine, 2020)
Diastolic dysfunction is condition of a stiff ventricle and a function of aging. It causes significant cardiovascular mortality and morbidity and in fact three million Americans are currently suffering from this condition[1; 2]. To date all the pharmacological clinical trials have been negative[3]. The lack of success in attenuating/ameliorating diastolic dysfunction stems from lack of duplication of myriads of clinical manifestation in pre-clinical settings[2; 4],[5]. Here we report, a novel genetically engineered mice which may represents a preclinical model of human diastolic dysfunction to some extent. Topoisomerase 2 beta (Top2b) is an important enzyme in transcriptional activation of some inducible genes through transient double-stranded DNA breakage events around promoter regions[6; 7]. We created a conditional, tissue-specific inducible Top2b knockout mice in the heart[8]. Serendipitously, echocardiographic parameter and more invasive analysis of left ventricular function with pressure-volume loops show features of diastolic dysfunction. This was also confirmed histologically. At the cellular level, the Top2b knockdown showed morphological changes and molecular signaling akin to human diastolic dysfunction. Reverse phase protein analysis showed activation of p53 and inhibition of cell survival signaling, Akt as the possible mediators of diastolic dysfunction. Finally, activation of p53 and inhibition of Akt were confirmed in myocardial biopsy samples obtained from human diastolic dysfunctional hearts. Thus, we report for the first time, a Top2b downregulated preclinical mice model for diastolic dysfunction which demonstrates that Akt and p53 are the possible mediators of the pathology, hence representing a novel and viable targets for future therapeutic interventions in diastolic dysfunction.